Effect of foliar spray with boron, seaweed extract on production and quality of apple cv. Starking Delicious - ديب, علي; صهيوني, فهد; بلال, عصام (Latakia University Journal -Biological Sciences Series, 2020)
The study was carried out at Blouta village of Al-Haffa city in Lattakia governorate, in apple orchard (Starking Delicious), total area of 5 dunums During the year 2019 on trees 20 years old and planted with (5*5) m spacing and grafted on Malus domestica Borkh rootstock. The experiment was designed in complete randomized way, and included four treatments with five replications and one trees in each replication: 1- (T1): control: Spray only with water. 2- (T2): Spray with Boron at concentration of 170 ppm. 3- (T3): Spray with algae extract Sprintal at concentration of 0.5 cm3/l (117 ppm Organic Carbon, 52.5 ppm Nitrogen). 4- (T4): spray with Boron at concentration of 170 ppm and spray with algae extract Sprintal concentration of 0.5 cm3/l (117 ppm Organic Carbon, 52.5 ppm Nitrogen). The study showed the following results: * Treatment of Boron at concentration of 170 ppm and algae extract at concentration of 0.5 cm3/l (117 ppm Organic Carbon, 52.5 ppm Nitrogen) spray alone or in combination increased the percentage of contract and reduced the fall of June, increased yield, and increased percentage of total soluble solids and total sugars. * Treatment of spray with Boron at concentration of 170 ppm and algae extract at concentration of 0.5 cm3/l (117 ppm Organic Carbon, 52.5 ppm Nitrogen) together gave the largest weight and volume of fruits.